PRAWO WYBORCZE A USTRÓJ DEMOKRATYCZNY - Łączkowski, Wojciech (Wydział Prawa i Administracji UAM, 2009)
One of the major reasons for socio-economic crises in democratic states and dissatisfaction of their citizens lies in the defects of the election procedures. This concerns, in particular, viewing the majority principle as an autonomous purpose of free elections. It is commonly acknowledged that the electoral act satisfies democratic standards if it guarantees a result which is consistent with the will of the majority of electors. Areas such as individual traits of candidates, as well as an objective value of their responses to referendum questions, become of secondary importance and are not covered by the electoral law. Such an approach seems to be correct and is usually not challenged, and is even regarded to be an axiom that needs no justification. The matter ceases to be so certain, though, when in the hierarchy of purposes in a democratic system, the common good and personal interest related to it are placed above the majority principle. Although such a situation is generally provided for by constitutions, in political practice, when solving specific matters, this is no longer obvious and the will of the majority gains absolute dominance. In the assessment of such a state of affairs, one should also take into consideration the fact that the communication techniques used in election campaigns may distort the truth about the candidates or the actual value attached to the particular options offered in the referendum outcomes. Hence it seems necessary to incorporate in the electoral act as well as in the constitution certain criteria that would guarantee minimal thresholds of moral character and would determine the substantive competence of candidates running for public office. What is more, the law should preclude referenda on matters the objective value of which does not depend on the views of the electors. This concerns in particular issues requiring specialist knowledge, which average electors do not have, and matters pertaining to the truth (natural, historical, economic, moral, etc.).
ELECTORAL LAW AND DEMOCRACY